Diagnóstico y diseño de una planta de tratamiento de agua potable para una comunidad de la vereda san isidro,municipio de san antonio del tequendama, departamento, de cundinamarca - López Mendivelso, Javier Alejandro (Universidad Antonio Nariño, 2022)
The use of drinking water treatment plants has become necessary in the country since it must be guaranteed that the resource in good conditions for human consumption of in accordance with the parameters established in the current regulations, all this due to the increase in the demand for this resource due to the population growth that occurs in the cities. The village of San Isidro is located in the municipality of San Antonio del Tequendama, in the department of Cundinamarca. The community is currently supplied of water from a spring in the upper part of the village, through a catchment system, consisting of an intake, a storage tank and a distribution tank, This is distributed through hoses to 5 families that have the concession with the CAR for the use of surface water. The community uses this water for human consumption and irrigation of crops, Users have identified that the water has color and turbidity at different times of the day, although these inconveniences are not constant, it gives us an idea of ​​the problems that could present in terms of water quality. having contaminated water produces damage to human health due to infections and diseases that can be contracted by pathogens present. The importance of having a good treatment system for these waters, which are human consumption becomes essential in this community, since it would bring a benefit in the quality of life, in addition to becoming a guide for the inhabitants of the municipality to implement these PTAPs in the different catchment sites. two